Vision-Based Digital Shadowing to Reveal Hidden Structural Dynamics of a Real Supertall Building - Donglian Gu; Qingrui Yue; Li Li; Chujin Sun; Xinzheng Lu (Engineering, 2024)
Vision-based digital shadowing is a highly efficient way to monitor the health of buildings in use. However, previous studies on digital shadowing have been limited to laboratory experiments. This paper proposes a novel computer-vision-based digital shadow workflow and presents its successful application in a real engineering case. In this case, a 345.8-m supertall building experienced unexpected shaking under normal meteorological conditions. This study established a digital shadow of the building using three-dimensional displacement measurements based on super-resolution monocular vision, revealing the hidden structural dynamics and inherent mechanical reasons for the abnormal shaking. The proposed digital shadowing workflow is a feasible roadmap for developing vision-based digital shadows of real-world structures using low-cost cameras. The abnormal vibration event in the supertall building considered in this study is the first of its type worldwide. The results of this study offer practical strategies and invaluable insights into the prevention and mitigation of this type of global risk, thereby contributing to the lifespan extension of buildings in use worldwide. Furthermore, with the increasing number of general sensing devices, such as surveillance cameras in cities, the proposed method may unleash the immense potential of general sensing devices in achieving the leap from structural health monitoring to city health monitoring.